Developing the teaching of the Holy Qur’an in elementary schools of Qur’an memorization in light of the approach of integration with Arabic language and science from the viewpoint of the faculty members in the Qur’anic Studies Department at King Saud University - Almusned, Shada Saleh; Al-Saadoun, Batoul Abdul Aziz (Journal of Educational and Psychological Sciences, 2021)
The study aimed to investigate the views of faculty members in the Qur’anic Studies Department at King Saud University on the development of teaching the Qur’an in elementary schools of Qur’an memorization in light of the approach of integration. To achieve this, the researcher used the descriptive method, and the questionnaire was used as a study tool. Where (30) members responded to the questionnaire, and the study found that the whole tool was obtained about the viewpoint of the faculty members in developing the teaching of the Holy Qur’an in light of the integration approach on an average (4.4 out of 5), indicating strong approval. Based on the results, the researcher recommended: to benefit from constructive learning theories, including the theory of meaningful learning in developing the teaching of the Noble Qur’an, to benefit from the experiences of schools with a religious orientation applied to the integration approach STREAM in accordance with Islamic law, and to qualify the teachers of the Holy Qur’an in accordance with modern trends in education.